Polyurethane-electrode modified to determine histamine in selected samples using chemical sensor - Febrianty Ratashya, Putri; Muhammad Abdurrahman, Munir; Fitria, Rahmawati; Adi, Gunawan (AIP Publishing, 2025)
Food safety is an imperative part of public health that needs to be considered to ensure human health. Histamine is a compound that is easily found in food protein. Thus, analyzing histamine in food before distributing it to the market is essential. The present study discusses applying chemical sensors to evaluate histamine levels in fish samples. The screen-printed electrode (SPE) was applied in this study and modified using bio-polyurethane (PU). The PU was produced using an electropolymerized approach, and the PU was characterized using FTIR to investigate the functional group, the cyclic voltammetry (CV) to study the conductivity, and electrochemical impedance spectroscopy (EIS) to study the resistance of PU after combined with histamine. Furthermore, differential pulse voltammetry (DPV) was employed to validate the histamine detection. The chemical sensor recorded a linear range from 10−3 – 10−1 nmol‧L−1 at the 0.002 nmol ‧L−1 limit of detection (LOD). The sensor can analyze histamine in selected samples at room temperature and obtain satisfactory outcomes. Furthermore, the sensor can be categorized as a fast technique and suitable for on-site analysis.